If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28 + -18 = x + -19 Combine like terms: 28 + -18 = 10 10 = x + -19 Reorder the terms: 10 = -19 + x Solving 10 = -19 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 10 + -1x = -19 + x + -1x Combine like terms: x + -1x = 0 10 + -1x = -19 + 0 10 + -1x = -19 Add '-10' to each side of the equation. 10 + -10 + -1x = -19 + -10 Combine like terms: 10 + -10 = 0 0 + -1x = -19 + -10 -1x = -19 + -10 Combine like terms: -19 + -10 = -29 -1x = -29 Divide each side by '-1'. x = 29 Simplifying x = 29
| 23x-4(4x-7)=28+7x | | 0=2x-(4/3)x | | 10-2m=3m | | 13x+6=11x-8 | | -6x-27=x^2 | | 12=8x-(4x-10) | | w+4=2w | | 11.42=3.2+7.6v+2.9 | | 9+35x-4x^2=0 | | mx^2+2x-m=0 | | 4(3x+-1)+2x=11 | | 2+6w=3w+20 | | Y=m(x+b) | | 1.76=4a-3.6a | | 21+2k=9k | | ab=8-cfora | | -(7/2)r+1(4/5)r=6(4/5) | | 4v=-12v+32 | | 6(x-4)+x=5(x-2) | | 10m-3p-(4m+20p)= | | 16(4y+8)=-8(9y+21) | | -12x+7X=5-2x^2 | | 6-3x=10x+2 | | 19=6+x | | 65x+9= | | 2n-14=-7+3n | | 8m-18=17+m | | 2t+9=17 | | -1.144=1-3.2a+4.54a | | 7m-24=-18+5m | | 8x-(3-x)= | | 3(2)x+1y=7 |